Hotel Characteristics and the Adoption of Demand Oriented Hotel Green Practices in Zimbabwe: A Regression - Njerekai, Cleopas (Africa Journals, 2021)
This paper determines the adoption levels of demand oriented green practices by hotels in Zimbabwe and then regresses these adoption levels with hotel characteristics. The study was prompted by the need to balance off the supply led skew in the country’s endeavours to project and promote itself as a green tourism destination and also to raise awareness of the need to accentuate the guest dimension in the greening of hotel operations as called for by various authors at a global scale. 50 out of the 124 registered hotels in the country constituted the study units. A quantitative research design was adopted for the research and the data was gathered through direct observation using an observation checklist. In terms of the first hypothesis, this study concluded that the adoption levels of demand oriented green practices by hotels in the country, was only 16% of those identified in existing literature. For the second hypothesis, the research rejects the alternate hypothesis and thus concludes that there is no significant relationship between hotel characteristics in the country and their adoption of demand oriented green practices. This conclusion is unexpected, surprising and a cause for concern for the country as one would expect higher quality hotels to be more sensitive to global trends on green issues. The study therefore suggests several ways by which hotels in the country edify the guest dimension in their greening efforts. Further research could be carried out to determine guest perceptions and attitudes towards these demand oriented green hotel practices.